2014
DOI: 10.4238/2014.january.21.22
|View full text |Cite
|
Sign up to set email alerts
|

Association of the GSTT1 polymorphism in upper aerodigestive tract cancer with tobacco smoking

Abstract: ABSTRACT. Polymorphisms in genes encoding xenobiotic-metabolizing enzymes might explain differences in the susceptibility to upper aerodigestive tract (UADT) cancers in individuals exposed to tobacco or other carcinogens. The present study aimed to evaluate the association of polymorphisms in the glutathione S-transferase (GST) candidate genes GSTM1, GSTT1, and GSTP1 with the risk of UADT cancers. GST gene polymorphisms were determined in 116 individuals with UADT cancer and 224 healthy controls using polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(39 reference statements)
0
7
1
Order By: Relevance
“…17 This same pattern was verified in our findings, since a higher OS rate was observed among the individuals with GSTT1 rs71748309 nonnull genotype, which was a risk factor for HNSCC in a previous case-control study carried out in the same population of present study. 14 In the present study, no significant association was observed between the polymorphisms GSTM1 rs4025935 null and CYP1A1 rs1048943 MspI and the OS of patients with HNSCC. A similar result was reported in a study conducted in the southeastern region of Brazil involving 153 patients diagnosed with HNSCC.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…17 This same pattern was verified in our findings, since a higher OS rate was observed among the individuals with GSTT1 rs71748309 nonnull genotype, which was a risk factor for HNSCC in a previous case-control study carried out in the same population of present study. 14 In the present study, no significant association was observed between the polymorphisms GSTM1 rs4025935 null and CYP1A1 rs1048943 MspI and the OS of patients with HNSCC. A similar result was reported in a study conducted in the southeastern region of Brazil involving 153 patients diagnosed with HNSCC.…”
Section: Discussioncontrasting
confidence: 72%
“…were enrolled. All individuals signed the consent form approved by the Institutional Ethics Committee of the State University of Santa Cruz -UESC (Protocol Number: 134/2007).From each volunteer, three milliliters of peripheral blood were obtained that was later used in the extraction of genomic DNA 14.…”
mentioning
confidence: 99%
“…The GSTT1 null genotype was less frequent among the investigated patients and healthy individuals and may indicate a reduced risk for cancer development. Similarly, studies on patients with HNSCC, such as the study carried in Brazilian population observed a lower frequency of the GSTT1 null genotype (16.8%) in healthy subjects (Brunialti, 2009), while Silva et al found a higher frequency of the GSTT1 positive genotype among healthy individuals (24.1%) (Silva et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have indicated that GSTP1 polymorphism is associated with various kinds of cancers, such as acute myeloid leukemia, lung cancer, breast cancer, colorectal cancer, brain tumor, and esophageal cancer (Cong et al, 2014;Silva et al, 2014;Song et al, 2014;Jaramillo-Rangel et al, 2015;Nasr et al, 2015;Sharma et al, 2015;Soto-Quintana et al, 2015;Zhou et al, 2015;Geng et al, 2016;Khabaz et al, 2016;Kimi et al, 2016). Several studies have also reported that GSTP1 polymorphism is associated with risk of gastric cancer in various populations, but the results were inconsistent (Nguyen et al, 2010;Zhang et al, 2011;Bao et al, 2012;García-González et al, 2012;Jing et al, 2012;Zhang et al, 2012;Ma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%